Potentiation of thrombin generation in hemophilia A plasma by coagulation factor VIII and characterization of antibody-specific inhibition. - Bhavya S Doshi; Bagirath Gangadharan; Christopher B Doering; Shannon L Meeks (PLoS ONE, 2012)
Development of inhibitory antibodies to coagulation factor VIII (fVIII) is the primary obstacle to the treatment of hemophilia A in the developed world. This adverse reaction occurs in 20-30% of persons with severe hemophilia A treated with fVIII-replacement products and is characterized by the development of a humoral and neutralizing immune response to fVIII. Patients with inhibitory anti-fVIII antibodies are treated with bypassing agents including recombinant factor VIIa (rfVIIa). However, some patients display poor hemostatic response to bypass therapy and improved treatment options are needed. Recently, we demonstrated that fVIII inhibitors display widely variable kinetics of inhibition that correlate with their respective target epitopes. Thus, it was hypothesized that for antibodies that display slow rates of inhibition, supplementation of rfVIIa with fVIII would result in improved thrombin generation and be predictive of clinical responses to this novel treatment regimen. In order to test this hypothesis, 10 murine monoclonal antibodies (MAbs) with non-overlapping epitopes spanning fVIII, differential inhibition titers, and inhibition kinetics were studied using a thrombin generation assay. Of the 3 MAbs with high inhibitory titers, only the one with fast and complete (classically defined as "type I") kinetics displayed significant inhibition of thrombin generation with no improvement upon supplementation of rfVIIa with fVIII. The other two MAbs that displayed incomplete (classically defined as "type II") inhibition did not suppress the potentiation of thrombin generation by fVIII. All antibodies that did not completely inhibit fVIII activity demonstrated potentiation of thrombin generation by the addition of fVIII as compared to rfVIIa alone. In conclusion, fVIII alone or in combination with rfVIIa corrects the thrombin generation defect produced by the majority of anti-fVIII MAbs better than single agent rfVIIa. Therefore, combined fVIII/rfVIIa therapy may provide better hemostatic control than current therapy in some patients with anti-fVIII inhibitors.